Conduction mechanisms in diamond-like carbon thin films prepared by PECVD method - Ab. Kaderld, Mohd. Azamnie (2010)
The aim of this study is to prepare thin films of diamond-like carbon (a-C:H) and to determine the conduction mechanisms in the diamond-like carbon thin films. Diamond-like carbon (a-C:H) thin films were deposited on corning glass substrates using PECVD method. The samples were fabricated in Al/a-C:H/Al structures in order to study the conduction mechanisms through the thin films. Current-voltage (IV) measurements were carried out using an electrometer. The I-V curves of the diamond-like carbon thin films at 84 nm and 110 nm show the features of ohmic characteristics in the lower field region (E < 2X107 V/m). In the higher field region (E > 2X107 V/m), the I-V characteristics of the diamond-like carbon thin film at 110 nm show the conduction in the diamond-like carbon thin film follows space-chargelimited current (SCLC) mechanism. The conduction mechanisms in the diamond-like carbon thin films were influenced by the thickness of the films.